Computer-assisted assessment of segmental bimaxillary surgery using voxel- and surface-based registration: A comparative study - Michael Boelstoft Holte; Alexandru Diaconu; Else Marie Pinholt (Elsevier, 2024)
The purpose of the present study was to compare the precision and reliability of voxel- and surface-based registration for computer-assisted assessment of the surgical accuracy and postoperative stability of segmental bimaxillary surgery. Three-dimensional translational and rotational measurements were performed by two observers using voxel- and surface-based registration. The precision and reliability of the measurements were calculated by the mean absolute differences (MAD) and intraclass correlation coefficients (ICC) at 95 % confidence intervals. A paired t-test or the non-parametric equivalent, Wilcoxon signed-rank test, was applied to statistically evaluate whether the precision of voxel- and surface-based registration was statistically significantly different (p < 0.05). Voxel-based registration had high precision (MAD <0.44 mm/0.92°) and excellent reliability, ICC [0.82-1.00]. The precision of surface-based registration was lower (MAD <0.56 mm/1.45°) and the reliability ranged from poor to excellent for the different bone segments, ICC [0.33-1.00]. Both registration techniques had high precision and excellent reliability for the assessment of the surgical accuracy, and the error margin of both techniques was clinical irrelevant. However, the increased precision of voxel-based registration was statistically significant (p < 0.05) for the maxillary segments and the chin, and the stability measurement error (ranging up to 1.58 mm and 4.46°) introduced by surface-based registration may be considered clinical relevant for these bone segments. Within the limitations of the present comparative study, voxel-based registration generally exhibited higher precision and reliability than surface-based registration for the surgical accuracy and postoperative stability assessment of segmental bimaxillary surgery.